Fiber-Like Radio Enabled by Fluid Antennas and Hybrid Sub-Connected Active/Passive RIS - Ntougias, Konstantinos; Krikidis, Ioannis (IEEE Global Communications Conference (Online), 2024)
A disruptive radio communication paradigm is proposed, where the dynamic channel reconfiguration capability of the emerging fluid antennas (FA) and hybrid reflecting intelligent surfaces (RIS) technologies is exploited to ensure favorable propagation and substantially boost multiple-input multiple-output capacity in a cost-effective and energy-efficient manner, offering fiber-like user experience improvement. The joint optimization of RIS scheduling and beamforming, precoding, and FAs' positions is studied in a fully- or sub-connected active/passive RIS-aided multiple-input single-output broadcast channel with a FAs-equipped base station (BS), such that the energy efficiency is maximized subject to the BS's and RIS's power consumption constraints. An efficient iterative algorithm based on fractional programming techniques, the block coordinate ascent framework, big-M formulation, penalty-based optimization, and the gradient ascent method is developed to tackle this challenging mixed-integer nonlinear program. Numerical simulation results validate the proposed concept and unveil its significant performance gains over benchmarks.